STEAM learning implementation in Makassar: SWOT analysis - Naufal, Muhammad Ammar; Ramdhani, Nurfitriah; Syahid, Nurul Khatimah; Zahrah, Fadliyah; Nurfadya, Masyta; Hafid, Nur Aqidah; Dassa, Awi; Ihsan, Hisyam; Ahmad, Asdar (Journal of Education and Learning (EduLearn), 2024)
The aim of this study is to identify the strengths, weaknesses, opportunities, and threats (SWOT) of science, technology, engineering, art, and mathematics (STEAM) learning at the elementary school level in Makassar. This study employed a mixed methods approach, specifically the QUANqual type of explanatory sequential design. The survey method was used to collect and analyze quantitative data, while interviews and documentation methods were used for qualitative non-numerical data. The respondents consisted of elementary school teachers in Makassar who were selected using simple random sampling. The results showed that using SWOT analysis and internal strategic factors analysis summary-external strategic factors analysis summary (IFAS-EFAS) calculations, the strengths-opportunities (SO) strategy has the highest score of 4.27. In addition, the weaknesses-opportunities (WO), strengths-threats (ST), and weaknesses-threats (WT) strategies received consecutive scores of 3.25, 2.71, and 1.69, respectively. It suggests that STEAM learning in Makassar is in a growth stage due to its strengths and opportunities that support the development of STEAM education in the city.